Proceedings of the Fourth International Workshop on the Identification of Dark Matter (World Scientific, 2003)
This book contains written versions of the presentations made at the 4th International Workshop on the Identification of Dark Matter (IDM 2002), held in York, UK, in September 2002. The objective of this workshop series is to assess the status of work attempting to identify what constitutes dark matter — in particular, to consider the techniques being used, how successful they are, and what new techniques are likely to improve prospects for identifying likely dark matter candidates in the future. At IDM 2002 special emphasis was placed on recent results obtained in searches for baryonic and non-baryonic dark matter. The proceedings include reviews of major topics on dark matter, as well as short contributed talks.